Publication productivity of Indian scientists in groundnut research : A bibliometric study. Issue 1 (2nd January 2018) - Dhoble, Shilpa; Kumar, S.; Kumar, Surendra
Abstract : The paper finds out the publication productivities of scientists on groundnut research in India. Analyses 3875 papers retrieved for the period 14 years (2000 -2013) from CAB Direct. Average activity index of India in the world is 103.12%. Journals have been used to publish 97.47% of research publications. Relative growth rate have decreased from 2000 to 2013. Growth of groundnut research is calculated by exponential, linear and logistic models. 74% of papers published in collaboration of two, three and four authors